Treatment of venous thromboembolism in patients with cancer: What news from clinical trials?. Issue 164 (April 2018) - Verso, Melina; Franco, Laura; Giustozzi, Michela; Becattini, Cecilia; Agnelli, Giancarlo
Abstract: About 15% of patients with cancer experience one or more episodes of venous thromboembolism (VTE) during the course of their disease. In patients with cancer, VTE has a substantial impact on the quality of life and care. Current guidelines recommend low-molecular-weight heparin (LMWH) as first choice therapy for long-term anticoagulation in cancer patients with VTE. However, there are several practical issues concerning the long-term use of these anticoagulants. In the last years, several direct oral anticoagulants (DOACs) have emerged as alternatives to heparins and vitamin K antagonists for the treatment of VTE, but data regarding both efficacy and safety of DOACs in the subgroup of patients with cancer treatments were limited. The results of two studies evaluating the clinical benefit of treatment of VTE with direct oral anticoagulants in patients with cancer have been recently presented. Several studies comparing DOACs with LMWH are currently ongoing.